ANALYSIS VIOLATION AND IMPLEMENTATION OF JOURNALISTIC CODE ETHICS ON ONLINE MEDIA OKEZONE.COM - Raskyansyah Dwiki Ananda; Dika Shafitri; Wahyunengsih (Universitas Islam Negeri Mataram, 2022)
This study aims to find out how to implement a journalistic code of ethics in order to understand the forms and reasons for the occurrence of violations in a news article, so that they can find solutions to these violations. This study uses an approach with the method of observation. The object of this research is the online media okezone.com in the national section. From the results of the research conducted, it can be said that the online media okezone.com has implemented a journalistic code of ethics well and professionally in opening a news.